Empirical models of consumer behavior - Aviv Nevo (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2010)
Models of consumer behavior play a key role in modern empirical Industrial Organization. In this paper, I survey some of the models used in this literature. In particular, I discuss two commonly used demand systems: multi-stage budgeting approaches and discrete choice models. I motivate their use and highlight some key modeling assumptions. I next briefly discuss key issues of estimation, and conclude by summarizing some extensions.
Keywords: 330; Industrial Organization; Demand Estimation; Differentiated Products; Almost Ideal Demand System; Discrete Choice; Industrieökonomik; Marktstruktur; Konsumentenverhalten; Diskrete Entscheidung; Nachfragesystem; Theorie